1980
DOI: 10.1093/infdis/142.4.602
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Interaction in Vitro with Use of Three Antibiotics Simultaneously against Pseudomonas maltophilia

Abstract: An abbreviated three-dimensional checkerboard titration method was devised to determine whether synergistic interaction of three antimicrobial agents could be found against multidrug-resistant bacteria. Pseudomonas maltophilia was used as the test organism because of its resistance to most commercially available antimicrobial agents, including those active against Pseudomonas aeruginosa. Three-dimensional isobolograms with concave surfaces were formed when synergy occurred. Triple combinations of gentamicin-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 6 publications
2
18
0
1
Order By: Relevance
“…1). Synergy for three antibiotics has been defined by several investigators as a fractional sum of Ͻ1.0 (⌺FIC of Ͻ1.0) (3,27). Plotted values showing concave surface areas on the isobolograms correspond to synergy, and convex areas represent antagonism (3,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Synergy for three antibiotics has been defined by several investigators as a fractional sum of Ͻ1.0 (⌺FIC of Ͻ1.0) (3,27). Plotted values showing concave surface areas on the isobolograms correspond to synergy, and convex areas represent antagonism (3,27).…”
Section: Discussionmentioning
confidence: 99%
“…A bactericidal effect was defined as Ն99.9% killing of the starting inoculum. FICs of Ͻ1.0, 1.0, and Ͼ1.0 were used to define synergy, addition, and antagonism, respectively, according to previously published methods (3,27). Time-kill studies were also performed according to earlier described techniques (7,17).…”
Section: Methodsmentioning
confidence: 99%
“…All study isolates were susceptible to TMP-SMX. Yu et al (40) found that the addition of rifampin to TMP-SMX plus carbenicillin resulted in consistent synergy by the checkerboard method. Confirmation of these results by time-kill studies was performed with one isolate only and may not adequately reflect the behavior of all strains.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, various antibiotic combinations yielded additive or synergistic effects against this microorganism, notably timentin + cotrimoxazole [49], fluoroquinolones + extended spectrum ß-lactams or ami- noglycosides [49,52], cotrimoxazole + polymyxin B [51], and ceftazidime + trovafloxacin [50]. Also, triple combinations of antibiotics (cotrimoxazole + carbenicillin + rifampin or gentamicin + carbenicillin + rifampin) were synergistically active against S. maltophilia [10,54].…”
Section: Introductionmentioning
confidence: 99%